Short-Term Monitoring of Geogenic Soil CO2 Flux in a Non-Volcanic and Seismically Inactive Emission Site, South Korea - Kim, Chan Yeong; Yu, Soonyoung; Oh, Yun-Yeong; Chae, Gitak; Yun, Seong-Taek; Shinn, Young Jae (Frontiers in Earth Science, 2021)
Temporal changes of soil CO2 flux (FCO2) and soil CO2 concentration ([CO2]v) were surveyed in a natural CO2 emission site to characterize the factors controlling the short-term temporal variation of geogenic FCO2 in a non-volcanic and seismically inactive area. Due to a lack of long-term monitoring system, FCO2 was discontinuously measured for three periods: Ⅰ, Ⅱ at a high FCO2 point (M17) and Ⅲ about 30 cm away. Whereas [CO2]v was investigated at a point (60 cm depth) for all periods. A 2.1 magnitude earthquake occurred 7.8 km away and 20 km deep approximately 12 hours before the period Ⅱ. The negative correlation of FCO2 with air pressure suggested the non-negligible advective transport of soil CO2. However, FCO2 was significantly and positively related with air temperature as well, and [CO2]v showed different temporal changes from FCO2. These results indicate the diffusive transport of soil CO2 dominant in the vadose zone, while the advection near the surface. Meanwhile [CO2]v rapidly decreased while an anomalous FCO2 peak was observed during the period Ⅱ, and the CO2 emission enhanced by the earthquake was discussed as a possible reason for the synchronous decrease in [CO2]v and increase in FCO2. In contrast, [CO2]v increased to 56.8 % during the period Ⅲ probably due to low gas diffusion at cold weather. In addition, FCO2 was low during the period Ⅲ and showed different correlations with measurements compared to FCO2 at M17, implying heterogeneous CO2 transport conditions at the centimeter scale. The abnormal FCO2 observed after the earthquake in a seismically inactive area implies that the global natural CO2 emission may be higher than the previous estimation. The study result suggests a permanent FCO2 monitoring station in tectonically stable regions to confirm the impact of geogenic CO2 to climate change and its relation with earthquakes.